Performance of electronics e-commerce during the COVID-19 pandemic: a comparative analysis (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective(s): This study aimed to analyze the performance of electronics e-commerce during the pandemic and verify which were the most used resources in this process, listing the digital marketing strategies used to boost online sales within organizations. Method(s): Thus, a basic, descriptive, and quantitative research was developed in the first half of 2022, when a structured questionnaire was applied to the e-commerce of electronics in Sananduva, Rio Grande do Sul, Brazil. By the results presented, it was found that digital marketing is important for companies and organizations that seek to apply it on social media, in which the number of users and consumers has increased. It was found that 37% of companies believe that digital marketing has increased the dissemination of products and services and improved communication and connection with customers. Results: It is concluded that the interactivity that digital marketing provides between market and consumer has improved the approach of companies with their potential customers, since the internet offers an opening to expose products and services, in addition to knowing the opinion of the public. Contributions: It is suggested to verify consumer behavior and e-commerce after the pandemic period in the municipality of Sananduva, with the possibility of extending the study to the region.
Keywords: digital marketing; social media; pandemic